Etične dileme pri obravnavi v zdravilišču - Lukšič-Gorjanc, Mateja (Rehabilitacija (Ljubljana), 2017)
Ethical dilemmas in rehabilitation medicine are becoming increasingly frequent, and are associated with progress in medicine, an evolving health care system, widespread information technologies, and societal changes. Rehabilitation in health resorts often involves a variety of ethical dilemmas during patients' treatment, such as those concerning institutional ethics, professional practice and clinical decision making. The exchange of new knowledge and acquired experiences eases rehabilitation professionals' work, relieves their stress and improves results.
Keywords: ethical issues; Ethics; etične dileme; health resort; rehabilitacija; Rehabilitation; vocational rehabilitation; zdravilišča